PC / PCTG composite material and preparation method and application thereof
By using specific parts by weight of SMA resin, organophosphorus-based flame retardant and titanate in PC/PCTG composites, the problem of insufficient light transmittance and flame retardancy in the prior art is solved, and high material transmissibility is achieved Improved light rate, heat resistance and flame retardancy, suitable for applications in specific scenarios.
Patent Information
- Application Number
- CN202411499767.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing PC/PCTG composites have shortcomings in improving light transmittance, heat resistance and flame retardancy. Conventional flame retardant methods will lead to a decrease in transparency and are difficult to meet the application requirements of specific scenarios.
By adding specific parts by weight of SMA resin, organophosphorus-based flame retardant and titanate to the PC/PCTG composite, the interface binding force and flame retardant performance are synergistically improved, ensuring light transmittance while improving heat resistance and solvent resistance while ensuring the light transmission. sex.
It realizes good light transmittance, heat resistance, solvent resistance and flame retardancy of PC/PCTG composite materials, and meets application needs in specific scenarios, such as transparent windows and lighting parts for electronics and household appliances.
Smart Images

Figure BDA0005102276900000061 
Figure BDA0005102276900000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified PC / PCTG composite materials, in particular to a PC / PCTG composite material and a preparation method and application thereof. Background Art
[0002] Polycarbonate (PC) is an engineering plastic with excellent comprehensive performance. It has the advantages of excellent toughness, good dimensional stability, high light transmittance and flame retardancy. It is widely used in electronic products, such as printers, monitors, computers, game consoles, electronic pens, etc. However, polycarbonate also has problems such as poor solvent resistance and reduced transparency after being made into V0 flame retardant grade, which limits its application in some scenes that require solvent resistance, flame retardancy and heat resistance, such as transparent windows of kitchen appliances, transparent lighting parts, etc. The solvent resistance of polycarbonate is usually improved by adding a second component with better solvent resistance, such as polybutylene terephthalate, polyethylene terephthalate, etc., but the limiting oxygen index of these components is relatively high, which will cause the flame retardant performance of PC to deteriorate after addition, and the conventional technical solutions for improving flame retardant performance usually cause the light transmittance of polycarbonate to decrease. Therefore, with the expansion of the application field of polycarbonate, the level of requirements for material performance continues to increase.
[0003] In order to solve the above technical problems, PC / PCTG composite materials have been developed in the prior art, which combine the advantages of PC and PCTG and have the characteristics of high light transmittance and good solvent resistance. However, in practical applications, the PC / PCTG composite material system still has problems such as loss of light transmittance when using conventional flame retardant means, and the heat resistance and solvent resistance cannot be well improved. Therefore, a PC / PCTG composite material with good light transmittance, heat resistance, solvent resistance and flame retardancy that meets the application requirements of specific scenarios has broad application prospects. Summary of the invention
[0004] Based on this, the object of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a PC / PCTG composite material with good light transmittance, heat resistance, solvent resistance and flame retardancy.
[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: a PC / PCTG composite material, comprising the following components in parts by weight: 55-75 parts of PC resin, 20-35 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol ester (PCTG resin), 1-5 parts of maleic anhydride-styrene random copolymer (SMA resin), 3-7 parts of organophosphorus flame retardant, and 0.1-0.5 parts of titanate; the mass percentage of maleic anhydride in the SMA resin is ≥13%.
[0006] In the PC / PCTG system, the present invention can improve the solvent resistance, flame retardancy and heat resistance of the polycarbonate composite material while ensuring good light transmittance through the synergy of SMA resin, organic phosphorus flame retardant and titanate with specific weight parts and specific components.
[0007] The present invention improves the interface bonding force of the system of PC and PCTG by selecting a specific weight portion of SMA resin, and can establish a connection between molecular chains. If the amount of SMA resin added is too little, it cannot establish a good connection between the molecular chains; if the amount of SMA resin added is too much, the overall flame retardant performance of the PC / PCTG composite material will decrease. The present invention better improves the interface bonding force of PC and PCTG by using an SMA resin with a specific mass percentage of maleic anhydride, can establish a connection between the molecular chains, resist deformation, and increase heat resistance.
[0008] The present invention selects specific weight portions of an organic phosphorus flame retardant, a titanate and an SMA resin. On the one hand, the titanate and the organic phosphorus flame retardant work together to improve the flame retardant properties of the PC / PCTG composite material system. On the other hand, the titanate can be combined with a specific SMA resin to promote the breaking of the molecular chains of PC and PCTG while allowing PC and PCTG to be tightly combined with each other, further affecting the light transmittance while improving the solvent resistance and heat resistance of the PC / PCTG composite material.
[0009] Preferably, the maleic anhydride grafting rate of the present invention can be determined by infrared spectroscopy: a sample of fixed thickness is tested using a Fourier transform infrared spectrometer to obtain characteristic absorption peaks of the infrared spectrum, and the grafting rate of maleic anhydride can be calculated by comparing the ratio of the carbonyl and methylene absorption intensities.
[0010] Preferably, the weight percentage of the PC resin in the PC / PCTG composite material is not less than 50%.
[0011] Preferably, the PC / PCTG composite material comprises the following components in parts by weight: 60-70 parts of PC resin, 25-30 parts of PCTG resin, 1.5-3 parts of SMA resin, 4-5 parts of organophosphorus flame retardant, and 0.3-0.4 parts of titanate.
[0012] The inventors found in the actual experimental process that the weight of PC resin, PCTG resin, SMA resin, organophosphorus flame retardant, and titanate will further affect the overall light transmittance, heat resistance, solvent resistance, and flame retardancy of the PC / PCTG composite material system. When the weight of the PC resin, PCTG resin, SMA resin, organophosphorus flame retardant, and titanate is within the above range, the overall light transmittance, heat resistance, solvent resistance, and flame retardancy of the PC / PCTG composite material system are better.
[0013] Preferably, the mass percentage of maleic anhydride in the SMA resin is 13-27%.
[0014] Preferably, the number average molecular weight of the PC resin is 18000-30000; and the intrinsic viscosity of the PCTG resin is 0.58-0.92 dl / g.
[0015] Optionally, the weight of the PC resin is 55 parts, 58 parts, 60 parts, 61 parts, 63 parts, 65 parts, 68 parts, 70 parts, 71 parts, 73 parts, 75 parts, or any two of the range values; the weight of the PCTG resin is 20 parts, 21 parts, 23 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, or any two of the range values; the weight of the SMA resin is 1 part, 1.5 parts, 2 parts, 2.3 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, or any two of the range values; the weight of the organophosphorus flame retardant is 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 6 parts, 6.5 parts, 7 parts, or any two of the range values; the weight of the titanate is 0.1 parts, 0.3 parts, 0.5 parts, or any two of the range values.
[0016] Optionally, the mass percentage of maleic anhydride in the SMA resin is 13%, 15%, 18%, 19%, 22%, 23%, 25%, 27% or any two of the range values. The number average molecular weight of the PC resin is 18000, 20000, 25000, 26000, 28000, 30000 or any two of the range values. The intrinsic viscosity of the PCTG is 0.58dl / g, 0.60dl / g, 0.62dl / g, 0.65dl / g, 0.7dl / g, 0.79dl / g, 0.82dl / g, 0.87dl / g, 0.89dl / g, 0.92dl / g or any two of the range values.
[0017] Preferably, the organophosphorus flame retardant is at least one of phosphate and phosphazene, and the titanate is at least one of tetrabutyl titanate, isopropyl titanate, propyl dioleyloxy (dioctyl phosphate) titanate, propyl dioleyloxy (dioctyl phosphate) titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl trioleyloxy titanate, isopropyl tri(dodecylbenzenesulfonic acid) titanate, isopropyl tri(dioctyl pyrophosphate) titanate, isopropyl tri(dioctyl pyrophosphate) ethylene titanate, and tetraisopropyl di(dioctyl phosphite) titanate.
[0018] Preferably, the PC / PCTG composite material further comprises 0.1-1 parts of a processing aid, wherein the processing aid is at least one of a lubricant and an antioxidant.
[0019] Optionally, the weight portion of the antioxidant is 0.1-0.5 parts, and the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant, such as antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), etc.
[0020] Optionally, the weight portion of the lubricant is 0.1-0.5 parts, and the lubricant is at least one of stearates, stearic acid esters, and ethylene bis stearic acid amides, such as pentaerythritol stearate, zinc stearate, and the like.
[0021] In addition, the present invention provides a method for preparing the PC / PCTG composite material, comprising the following steps: mixing the components in proportion, melt-extruding, and granulating to obtain the PC / PCTG composite material.
[0022] Preferably, the temperature of the melt extrusion is 210-260°C.
[0023] Furthermore, the present invention provides an application of the PC / PCTG composite material in the field of electronic appliances or household appliances. The PC / PCTG composite material can be applied to transparent windows of household appliances, transparent lighting accessories, etc. Specifically, the PC / PCTG composite material can be applied to transparent windows of washing machines, rice cookers, microwave ovens, etc., as well as transparent windows of electronic cigarettes, electronic pens, etc.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention improves the interfacial bonding force of the system phase of PC and PCTG by selecting a specific weight portion of SMA resin, and can establish a connection between the molecular chains. If the amount of SMA resin added is too little, it cannot establish a good connection between the molecular chains; if the amount added is too much, the overall flame retardant properties of the PC / PCTG composite material will decrease. The present invention better improves the interfacial bonding force of PC and PCTG by using an SMA resin with a specific mass percentage of maleic anhydride, can establish a connection between the molecular chains, resist deformation, and increase heat resistance. If the mass percentage of maleic anhydride is too low, the connection between the molecular chains is weak; if the mass percentage of maleic anhydride is too high, micelles are easily formed, resulting in a decrease in transmittance.
[0025] The present invention selects specific weight portions of an organic phosphorus flame retardant, a titanate and an SMA resin. On the one hand, the titanate and the organic phosphorus flame retardant synergistically improve the flame retardant properties of the PC / PCTG composite material system. On the other hand, the titanate can be combined with a specific SMA resin to promote the breaking of the molecular chains of PC and PCTG while allowing PC and PCTG to be closely combined with each other, further affecting the light transmittance while improving the solvent resistance and heat resistance of the polycarbonate composite material. DETAILED DESCRIPTION
[0026] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0027] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:
[0028] PC resin-1: number average molecular weight is 20000, H-3000F, Mitsubishi, Japan.
[0029] PC resin-2: number average molecular weight is 28000, S-2000F, Mitsubishi, Japan.
[0030] PCTG resin-1: TX1501HF, Eastman Chemical, the intrinsic viscosity of the PCTG resin is 0.58 dl / g.
[0031] PCTG resin-2: DN-011, Eastman Chemical, the intrinsic viscosity of the PCTG resin is 0.7 dl / g.
[0032] PCTG resin-3: Z6018, Eastman Chemical, the intrinsic viscosity of the PCTG resin is 0.92 dl / g.
[0033] SMA resin-1: maleic anhydride-styrene random copolymer, SMA-700, the mass percentage of maleic anhydride in the SMA resin is 18%, Hua Wen.
[0034] SMA resin-2: maleic anhydride-styrene random copolymer, SZ23110, the mass percentage of maleic anhydride in the SMA resin is 23%, POLYSCOPE.
[0035] SMA resin-3: maleic anhydride-styrene random copolymer, SZ15170, the mass percentage of maleic anhydride in the SMA resin is 15%, POLYSCOPE.
[0036] SMA resin-4: maleic anhydride-styrene random copolymer, SMA-725K, the mass percentage of maleic anhydride in the SMA resin is 25%, Hua Wen.
[0037] SMA resin-5: maleic anhydride-styrene random copolymer, SMA EF80, the mass percentage of maleic anhydride in the SMA resin is 10%, POLYSCOPE.
[0038] Organic phosphorus flame retardant-1: bisphenol A bis(diphenyl phosphate) BDP, commercially available.
[0039] Organic phosphorus flame retardant-2: phosphazene, commercially available.
[0040] Titanate-1: tetrabutyl titanate, commercially available.
[0041] Titanate-2: Tetraisopropyl di(dioctylphosphite) titanate, commercially available.
[0042] The antioxidant is a composite of a commercially available hindered phenol antioxidant 1010 and a commercially available phosphite antioxidant 168 in a mass ratio of 1:1.
[0043] Examples 1-12 and Comparative Examples 1-5
[0044] The components and weight proportions of the PC / PCTG composite material of the present invention and the comparative example are shown in Table 1-2. The preparation method of the PC / PCTG composite material comprises the following steps: mixing the components in proportion, melt extruding, and granulating to obtain the PC / PCTG composite material. The melt extrusion condition is: 210-260°C.
[0045] Performance Testing
[0046] Heat resistance test: According to the test standard ASTM D648-2016, the heat deformation temperature HDT is measured with a 6.4 mm thick bar placed flat under a load of 1.82 MPa, and the results are recorded in °C.
[0047] Flame retardancy test: According to UL-94-2018; the injection molding specification is a standard test piece of 125*13*3.0mm, and it is tested using a vertical burning tester; according to the standard, the test results include V-0, V-1, V-2, V-2 cannot be achieved, etc.
[0048] Light transmittance test: Tested according to ASTM D1003-2013 standard;
[0049] Solvent resistance test: According to ASTM D543-2014, peanut oil was applied to the tensile strength test specimen (specimen thickness 3.2 mm) in a 1.0% strain fixture and the appearance changes were observed. The specimens were divided into four grades according to the severity of the cracks: A (no cracks), B (slight cracks), C (severe cracks) and D (breaks).
[0050] The results of the performance test are shown in the following table.
[0051] Table 1
[0052]
[0053]
[0054] Table 2
[0055] Components (parts by weight) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PC resin-1 66 66 66 66 66 PCTG resin-1 26 26 26 15 45 SMA resin-1 0 2.4 0 2.4 2.4 SMA Resin-5 2.4 0 0 0 0 Organic phosphorus flame retardant-1 4.5 4.5 4.5 4.5 4.5 Titanate-1 0.3 0 0.3 0.3 0.3 Antioxidants 0.1 0.1 0.1 0.1 0.1 Heat deformation temperature(℃) 86 89 85 102 77 Flame retardant properties V1 V1 V2 V0 V2 Light transmittance (%) 88 88 89 88 88 Solvent resistance A A A C A
[0056] It can be seen from the above table that the PC / PCTG composite materials prepared in the embodiments of the present invention can meet the solvent resistance of A, light transmittance ≥85%, flame retardancy V0, and heat deformation temperature ≥80°C. At the same time, they have good light transmittance, heat resistance, solvent resistance and flame retardancy, meeting the application requirements of specific scenarios.
[0057] From the comparison of Examples 1-4, it can be seen that when the mass percentage of maleic anhydride in the SMA resin is 13-27%, it has good light transmittance, heat resistance, solvent resistance and flame retardancy, meeting the application requirements of specific scenarios.
[0058] By comparing Example 1 and Examples 9-12, it can be seen that when the PC resin is 60-70 parts, the PCTG resin is 25-30 parts, the SMA resin is 1.5-3 parts, the organophosphorus flame retardant is 4-5 parts, and the titanate is 0.3-0.4 parts, the prepared PC / PCTG composite material has better light transmittance, heat resistance, solvent resistance and flame retardancy.
[0059] From the comparison of Example 1 and Comparative Examples 1-3, it can be seen that when titanate, SMA resin and organophosphorus flame retardant work together, they have good light transmittance, heat resistance, solvent resistance and flame retardancy, meeting the application requirements of specific scenarios.
[0060] From the comparison of Example 1 and Comparative Examples 4-5, it can be seen that when the amount of PCTG added is too low, the solvent resistance test is C; when the amount of PCTG added is too high, the flame retardant performance is V2, and the heat resistance is poor, both of which do not meet the requirements.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PC / PCTG composite material, characterized in that: The invention comprises the following components in parts by weight: 55-75 parts of PC resin, 20-35 parts of PCTG resin, 1-5 parts of SMA resin, 3-7 parts of organic phosphorus flame retardant and 0.1-0.5 parts of titanate; the mass percentage of maleic anhydride in the SMA resin is ≥13%.
2. The PC / PCTG composite material according to claim 1, wherein The invention comprises the following components in parts by weight: 60-70 parts of PC resin, 25-30 parts of PCTG resin, 1.5-3 parts of SMA resin, 4-5 parts of organic phosphorus flame retardant and 0.3-0.4 parts of titanate.
3. The PC / PCTG composite material according to claim 1, wherein The mass percentage of maleic anhydride in the SMA resin is 13-27%.
4. The PC / PCTG composite material according to claim 1, wherein The organophosphorus flame retardant is at least one of phosphate ester and phosphazene; the titanate is at least one of tetrabutyl titanate, isopropyl titanate, propyl dioleyloxy (dioctyl phosphate acyloxy) titanate, propyl dioleyloxy (dioctyl phosphate acyloxy) titanate, isopropyl tris (dioctyl phosphate acyloxy) titanate, isopropyl trioleyloxy titanate, isopropyl tris (dodecylbenzenesulfonic acid) titanate, isopropyl tris (dioctyl pyrophosphate acyloxy) titanate, isopropyl tris (dioctyl pyrophosphate acyloxy) ethylene titanate, and tetraisopropyl di (dioctyl phosphite acyloxy) titanate.
5. The PC / PCTG composite material according to claim 1, wherein The number average molecular weight of the PC resin is 18000-30000; the intrinsic viscosity of the PCTG is 0.58-0.92 dl / g.
6. The PC / PCTG composite material according to claim 1, wherein The PC / PCTG composite material further comprises 0.1-1 parts of a processing aid, wherein the processing aid is at least one of a lubricant and an antioxidant.
7. A method for preparing the PC / PCTG composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are mixed in proportion, melt-extruded and granulated to obtain the PC / PCTG composite material.
8. Use of the PC / PCTG composite material according to any one of claims 1 to 6 in the field of electronic appliances or household appliances.
9. Use of the PC / PCTG composite material according to any one of claims 1 to 6 in transparent windows of electronic appliances or household appliances.
Citation Information
Patent Citations
Halogen-free flame retardant PC (poly carbonate) composition and preparation method thereof
CN104119658A
Silicon-containing polycarbonate and preparation method thereof
CN105860545A
Photodiffusion PC / PCTG composite material and preparation method thereof
CN109265953A
High-temperature-resistant impact-resistant transparent resin as well as preparation method and application thereof
CN114213813A
KR20240107293A
Cited By
Wear-resistant and stain-resistant PETG composite material and application thereof in preparation of furniture building materials
CN120209519A
Wear-resistant and stain-resistant petg composite material and application thereof in preparation of furniture building materials
CN120209519B
